Monitoring of the Earth's atmosphere at the Terskol Observatory: current status and prospects - Godunova, V.; Sosonkin, M. (Кинематика и физика небесных тел, 2005)
Continuous high-frequency (every minute) automatic measurements of surface ozone concentrations have been made at the high-altitude Terskol Observatory (on the slope of Elbrus mountain, the Northern Caucasus) since 2003. We present the main experimental results including seasonal variations and the main factors affecting ozone levels. Ozone concentrations in air at Terskol Peak (3100 m above sea level) show a distinct seasonal cycle with the highest concentrations during spring–summer period and a peak amplitude of about 85 ppbv. In autumn–winter period, the daily maximum ozone concentrations are typically around 40 ppbv.